Metaphorical maps as a means of developing speech imagery at classes of Russian as a foreign language - Nina L. Fedotova; Alexandra V. Burtseva; Inna V. Ryzhkova (Russian Language Studies)
The relevance of the study is conditioned by the need to develop speech imagery in foreigners studying Russian and to improve their communicative competence in speaking and writing. The aim of the study is to justify the use of metaphorical associative cards in teaching a foreign language and to suggest forms of working with metaphorical cards at classes of Russian as a foreign language. The feasibility and prospects of metaphorical associative cards are proved with empirical and analytical methods; a pedagogical experiment was conducted in a group of Chinese 3rd-year students of “Linguistics” at Peter the Great St. Petersburg Polytechnic University; oral statements of students produced when working with usual metaphors and with a metaphorical map were analyzed. Comparative analysis of students’ statements allowed us to interpret metaphorical associative cards as a tool for foreign language speech development, substantiate its expediency for the development of students’ speech imagery. The speech imagery is understood as a mechanism for forming an idea of a future statement. Together with speech actions, it takes part in the process of speech generation. The metaphorical map increases students’ creativity, allows them to move from combining template constructions to creating an original text idea. The study characterizes the functions of a metaphorical associative map at different stages of a student’s speech activity, gives recommendations for using them for developing creative speech abilities of foreign students and their speech imagery, and suggests scenarios for working with them at the classes of Russian as a foreign language. The study implies further search for ways of developing speech imagery and increasing the linguistic and didactic potential of metaphorical associative cards in teaching Russian as a foreign language. The results of the study are useful for teaching written and oral communication in a foreign language.